IMPLEMENTATION OF INVESTMENT FUNDS SHARING AGREEMENT IN SHARIA BANKING SYSTEM IN INDONESIA - Evita Isretno Israhadi (Diponegoro Law Review, 2020)
Mudharabah financing investment, also known as trust financing, is a method of distributing funds in Sharia banking to comply with the religious prohibition of interest on loans. However, the use of legal protection has not been maximized in increasing the growth of mudharabah financing investment products, especially for SMEs (Micro, Small and Medium Enterprises), due to the complicated process of filing and guarantees needed by the bank. This study, therefore aims to implement adequate investment funds sharing agreement in Indonesia’s Sharia Banking System for mudharabah investments to be felt in all categories. The result showed that regulatory restructuring is needed for the application of mudharabah investment to be a real sector driver without eliminating the purity of Islamic principles.